Health care reform : what it is, why it's necessary, how it works - Gruber, Jonathan (New York : Hill and Wang, 2011)
"A graphic explanation of the PPACA act"--Provided by publisher
A cure for what ails us -- Taming the two-headed beast --Through the past, darkly -- We the people...need to be insured -- Making it work in Massachusetts -- The Affordable Care Act. a.k.a. ACA -- Don't worry, we've got you covered -- Selling fear instead of facts -- Picking up the check -- Taking on cost control -- Keeping seniors safe and sound -- Good things on the horizon.
Keywords: United States; United States; United States; Popular Works -- United States; Popular Works -- economics| -- United States; Popular Works -- United States; Popular Works -- United States